Soluble Endothelial Selectin in Acute Lung Injury Complicated by Severe Pneumonia - Osaka, Daisuke (Ivyspring International Publisher, 2011)
Background: Pneumonia is still one of the most frequent causes of death in the elderly. Complication of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) by pneumonia makes patients very ill due to severe respiratory failure. Biomarkers that can discriminate the presence of complicating ALI/ARDS are required for early detection. The aim of this research was to investigate whether soluble endothelial selectin (sES) could be a biomarker for ALI. Methods: Serum sES levels were measured in 27 pneumonia patients, who were enrolled between April 2006 and September 2007. Among these patients, six had ALI or a condition that was clinically comparable to ALI (cALI). All patients who were enrolled were successfully treated and survived. Results: Circulating sES levels were elevated in pneumonia patients with ALI/cALI, and sES levels decreased following treatment of their pneumonia. Univariate and multivariate logistic regression analyses showed that sES was the only significant factor for identifying complicating ALI/cALI, independently of C-reactive protein (CRP) and lactate dehydrogenase (LDH). By receiver operating characteristic (ROC) curve analysis, the cut-off value for sES was 40.1 ng/mL, with a sensitivity of 0.8 and a specificity of 0.8. Conclusion: sES may be a useful biomarker for discriminating complicating ALI/cALI in patients with severe pneumonia.